Pengaruh Model Discovery Learning Berbantuan Media Kartu Kata Bergambar Terhadap Hasil Belajar Tematik - Kurnia Novtri Wulandari S.; Herman Lusa; Dalifa (JURIDIKDAS, 2023)
This study aims to determine the effect of discovery learning models assisted by pictorial word card media on Thematic learning on student learning outcomes. This research is quantitative research. The research method used was Quasi Experiment with the type of design The Matching Only Pretest-Posstest Control Group Design. The population of this study was first-grade students of SDN Gugus 10 Lebong Regency. The sample in this study was class I SDN 54 Lebong and Class I SDN 16 Lebong. The sampling technique uses Cluster Random Sampling. The total sample of 52 students consisted of class I SDN 54 Lebong totaling 25 students as the experimental class and class I SDN 16 Lebong totaling 27 students as the control class. The research instrument used was in the form of a knowledge learning test in the form of Multiple Choices given through Pretest and Posttest, for the learning outcomes aspects of attitudes and skills the instruments used were observation guidelines. The data analysis technique in this study is quantitative analysis using descriptive statistics and inferential statistics. Based on the results of inferential statistical analysis using the t-test. Based on the results of this study it is known that the value of t-count on SBDP subjects is 5.43 and in Indonesian Language subjects is 2.65 greater than t-table at a 5% significance level of 1.675. Thus the Ha hypothesis is proven and accepted. This shows that there are influences on student learning outcomes in Thematic learning that use discovery learning models assisted with pictorial word card media.